Effect of seed size on initial plant growth and grain yield of wheat - Bredemeier, Christian; Mundstock, Claudio Mario; Büttenbender, Daniel (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this work was to evaluate the effect of seed size on the initial plant growth and grain yield of wheat. The experiments were carried under chamber growth (20oC at day and 10oC at night; 12 hours light/day) and field conditions, with 300 seeds/m2 density. Treatments consisted of seeds with different size, classified according to the diameter (less than 3.0 mm to higher than 3.75 mm). Under controlled conditions, plants originated from larger seeds showed higher leaf emission rate, and their first three leaves had higher mass and length. These plants presented higher first tiller emission, higher tiller dry matter and more tillers/plants. The early advantages derived from larger seeds were not presented on final grain yield on the field.